Germination and Early Growth of Brachychiton populneus (Schott & Endl.) in Response to Different Shade Percentages and Sowing Depths. - Sherzad O. Hamad; Ako H. Mahmood; Narin S. Ali (Zanco Journal of Pure and Applied Sciences, 2023)
A tree's ability to develop and its full potential depends on the environment in which it grows, especially during its early growth and germination stage. Due to the importance of planting depth and shadowing % as two important parameters for seed germination and early seedling growth under nursery conditions, this experiment was conducted to generate Brachychiton populneus seedlings at the optimal depth. In this study, three levels of shade conditions were tested with depths of 0, 1, 2, and 3 cm, respectively (0 percent shade, 50 percent shade, and 75 percent shade, respectively). The experimental design was factorial complete randomized design (CRD) with four replications for each treatment. At the end of the trial final germination percentages and vegetative growth parameters were measured. The results indicated that the different sowing depths and shade percentage treatments had a great significant influence on germination percentage, stem length, basal stem diameter, leaf number, and root length either in separately or in combination between both. Mean of germination percentage under zero shade percentage (full sunlight) significantly better than those under 50 and 75 shade percentage. Furthermore, the highest germination percentage was 80 % when the seeds were sown under full sunlight (zero shade percentage) and in 1 cm deep or under 50% shade percentage and 2 cm deep. Our results will help forest nurseries to produce healthy and a high quality of B. populneus seedlings for better chance of plantation programs.